CProS: A web-based application for chemical production scheduling. (August 2022) - Misra, Shamik; Buttazoni, Lucas Ryan; Avadiappan, Venkatachalam; Lee, Ho Jae; Yang, Martin; Maravelias, Christos T.
Highlights: In this paper, we present CProS (C hemical pro duction S cheduling), a free-to-use web-based application (https://cpros.azurewebsites.net/ ) for chemical production scheduling. The application offers a graphical interface to model production facilities and provides an array of solution methods. The paper provides essential details on the models and methods used in the application, and a step-by-step guide to help the users navigate the interface. Abstract: While a large range of models and methods have been proposed in the literature for chemical production scheduling, very limited tools are available for researchers to test these methods. This communication describes a web-based application (CProS) that was recently developed to facilitate the generation and solution of chemical production scheduling instances. The application offers an interface through which a user can define an instance using the state-task network (STN) representation. Given an instance, the application then automatically generates a discrete-time STN-based mixed-integer linear programming (MIP) model. In addition, the user has the option to use three different solution methods: (1) tightening constraints; (2) a reformulation; and (3) a three-stage discrete-continuous algorithm. We showcase the functionality of the application through a case study.